(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
نفذت الدراسة بمركز اللاذقية لتربية وتطبيقات الأعداء الحيوية، ضمن بيت بلاستيكي في أثناء موسمين زراعيين 2005-2006 و2006-2007. شملت الدراسة ثلاث معاملات: 1- شاهد (نباتات فريز سليمة)، 2- نباتات فريز تم نشر الأكاروس العنكبوتي ذي البقعتين Tetranychus urticae Koch عليها 3- نباتات فريز تم نشر الأكاروس T. urticae عليها والمفترس الأكاروسي Phytoseiulus persimilis Athias-Henroit في مرحلة لاحقة. أظهرت النتائج الأثر السلبي للأكاروس T.urticae في نمو نباتات الفريز من خلال خفض عدد الأوراق الكلية على النبات ومحتواها من الكلوروفيل وتراجع مساحة ودليل المسطح الورقي، وانخفاض كفاءته التمثيلية وبفروق معنوية عن معاملتي الشاهد والمفترس. كما تبين أيضاً ارتفاع محتوى ثمار الفريز من النترات وفيتامين C في معاملة الفريسة وتفوقها معنوياً على معاملتي الشاهد والمفترس. إضافة إلى انخفاض كمية الإنتاج وارتفاع نسبة الثمار المشوهة في معاملة الفريسة. This study was carried out in a green house in Lattakia center for rearing natural enemies during 2005-2006 and 2006-2007. The study included three treatments: 1. control (healthy plants); 2. plants infected with the prey Tetranychus urticae; 3. plants infected with the prey and the predatory mite Phytoseiulus persimilis. Results showed that there was a negative effect of T.urticae in the prey treatment, where the control and predator treatments were significantly better in the total number of leaves/plant, foliage area, leaf area index, photo synthetic capacity, and chlorophyll concentrate. The contents of nitrate and ascorbic acid were high in the prey treatment with high significant difference in comparison with other treatments. The production was low in the prey treatment, and fruits were deformed too.